Total Congenital Anonychia. Issue 6 (November 2014) - Afsar, Fatma Sule; Karakuzu, Ali
Abstract Total or partial absence of nails at birth is rare. Anonychia can be inherited as an autosomal dominant or recessive trait. An otherwise healthy 4‐year‐old boy whose parents were first‐degree relatives was diagnosed with total congenital anonychia.